GE_GERICHTE P/19816/2017 vom 15. Juni 2022 - GE Cour de justice (2022)
ORDONNANCE PÉNALE;PRINCIPE DE L'ACCUSATION;COMPLÉMENT;PLAINTE PÉNALE;NULLITÉ;DIFFAMATION;CALOMNIE | CP.173; CP.174; CP.30; CP.32; CPP.353; CPP.354; CPP.322; CPP.9; CPP.329